A Comparison of capitation and fee for service provider payment mechanisms and their effects on cost of healthcare: a case study of the Avenue Hospital, Nairobi - Ochieng, Teddy Brian (Strathmore University, 2019)
Increasing health costs globally have resulted in more patients seeking pre-payment mechanisms for health insurance to avoid catastrophic expenditures. Insurers use capitation and fee for service models for reimbursement, but there is insufficient evidence on which is efficient or cost effective. This study uses retrospective panel data from the Avenue Hospital’s electronic medical records (EMR) to compare reimbursement costs using capitation and fee for service models by four Kenyan insurance companies. The costs were compared across similar illnesses in patients presenting at the outpatient department analyzing 3,694 patient visits over a six-month period. The mean costs for treating diseases were used for the analysis, which entailed comparing mean capitation costs to mean fee for service payments. The data was extracted using excel, sorted and filtered, then analyzed in pivot tables and pivot charts. Descriptive analysis was used to derive means and percentage counts that were presented in tables and bar graphs. The analyses revealed that capitation costs are 7.8% lower than the mean costs under the fee for service model. This difference was significant for three out of the four illnesses analyzed, the exception being hypertension. The results of the study concluded proved that payment of health costs by capitation was cheaper than fee for service. This in essence leads to a conclusion that capitation is a cheaper form of insurance than fee for service schemes. The results of the study can be used for further research on cost reduction in provider payment schemes and also inform policy on the relevance of insurance and utilization management in capitation in reducing health costs.
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Business Administration in Healthcare Management at Strathmore Business School
Keywords: Capitation; Service provider payment mechanisms; Healthcare cost; Avenue Hospital_Nairobi